S-Sulfocysteine Induces Seizure-Like Behaviors in Zebrafish - Plate, Jennifer; Sassen, Wiebke A.; Hassan, Ahmed H.; Lehne, Franziska; Köster, Reinhard W.; Kruse, Tobias (Frontiers in Pharmacology, 2019)
Sulfite is a neurotoxin, which is detoxified by the molybdenum cofactor (Moco)-dependent enzyme sulfite oxidase (SOX). In humans, SOX deficiency causes the formation of the glutamate analog S-Sulfocysteine (SSC) resulting in a constant overstimulation of ionotropic glutamatergic receptors. Overstimulation leads to seizures, severe brain damage, and early childhood death. SOX deficiency may be caused either by a mutated sox gene or by mutations in one of the genes of the multi-step Moco biosynthesis pathway. While patients affected in the first step of Moco biosynthesis can be treated by a substitution therapy, no therapy is available for patients affected either in the second or third step of Moco biosynthesis or with isolated SOX deficiency. In the present study, we used a combination of behavior analysis and vital dye staining to show that SSC induces increased swimming, seizure-like movements, and increased cell death in the central nervous system of zebrafish larvae. Seizure-like movements were fully revertible upon removal of SSC or could be alleviated by a glutamatergic receptor antagonist. We conclude that in zebrafish SSC can chemically induce phenotypic characteristics comparable to the disease condition of human patients lacking SOX activity.